The Validity of the Belis Marriage is Related yo the Right to Inherit Land in Hambapraing Village, East Sumba Regency - Arnold Paul Kurniawan Djae; I Nyoman Sukandia; I Wayan Kartika Jaya Utama (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Because there is a shift in the meaning of belis from a cultural tradition to something that is considered a burden and burdensome for men as the party who gives belis, this also causes the giving of belis to not be carried out in full before the marriage takes place. So from this it is very good to examine if the belis is not fully implemented whether the heirs' rights for the heirs will be obtained. Rather than this, this study uses an empirical legal research method by using a conceptual approach. Where the source of data for this research is obtained through primary data obtained through the results of interviews, observations and documentation. Secondary data is obtained through applicable laws and regulations. The data source is then analyzed with description techniques and legal discovery techniques in the field. The result of this study is that if the marriage status of the belis that has not been paid in full in Hambraping village, then the man will be obliged to prepare land and land for the woman who is in the village which is usually called Laku Longgamai which means that the woman is not allowed to visit the man's house and is only allowed once a month if the woman returns to her biological parents' house, It is also not allowed to stay overnight and stay overnight.